Application of The Case-Based Method to Critical Thinking Based on Learning Motivation in Students of The Population Geography Course - Yurni Suasti; Rahmanelli Rahmanelli; Bigharta Bekti Susetyo; Bayu Wijayanto; Ahyuni Ahyuni (Jurnal Penelitian Pendidikan IPA, 2026)
This study investigated the effectiveness of a case-based learning (CBL) approach in improving students’ critical thinking skills in the Population Geography course at Universitas Negeri Padang. A quasi-experimental design was employed involving two classes: an experimental class receiving CBL and a control class receiving conventional instruction. Students with low, medium, and high initial abilities participated in the study. Data were collected through classroom observations and pretest–posttest assessments of critical thinking and analyzed using an independent-samples t-test and N-gain analysis with SPSS. The pretest results indicated no significant difference between the experimental and control groups, confirming comparable initial abilities. However, the posttest revealed a significant improvement in the experimental group compared with the control group. The experimental class achieved a higher mean posttest score (14.56) than the control class (9.85), with N-gain values of 84% and 31%, respectively, indicating substantially greater learning effectiveness. Further analysis showed that learning motivation did not significantly interact with the implementation of CBL in influencing critical thinking. The findings demonstrate that case-based learning effectively enhances critical thinking skills in Population Geography, regardless of students’ motivation levels, and supports its integration into geography education to promote higher-order thinking